Deracemization of (RS)-1-[(4-methylselanyl)phenyl]ethanol and (RS)-1-[(4-ethylselanyl)phenyl]ethanol by strains of Aspergillus terreus - Assis, Leonardo Fernandes (Array, 2007)
The fungal strains Aspergillus terreus URM 3371 and A. terreus CCT 4083, isolated in Brazil, catalysed the deracemization of (RS)-1-[(4-methylselanyl)phenyl]ethanol (1) and (RS)-1-[(4-ethylselanyl)phenyl]ethanol (2). Different mass of whole fungal cells (1–5 g), pH values (4 and 7), biotransformation temperature (20 and 32 °C) and additives (ethanol, butanol, propanol and cyclohexanol) were employed in attempt to improve product yield and selectivity. The A. terreus strain URM 3371 transformed (RS)-1 into (+)-(R)-1 with high enantiomeric excess (e.e.³98 %), good conversion (³98 %) and acceptable yield (53 %)